Novel hybrid silicon-lipid nanoparticles deliver a siRNA to cure autosomal dominant osteopetrosis in mice. Implications for gene therapy in humans - Antonio Maurizi; Piergiorgio Patrizii; Anna Teti; Flavia Maria Sutera; Paulina Baran-Rachwalska; Chris Burns; Uttom Nandi; Michael Welsh; Nissim Torabi-Pour; Ashkan Dehsorkhi; Suzanne Saffie-Siebert (Elsevier, 2023)
Rare skeletal diseases are still in need of proper clinically available transfection agents as the major challenge for first-in-human translation relates to intrinsic difficulty in targeting bone without exacerbating any inherent toxicity due to used vector. SiSaf's silicon stabilized hybrid lipid nanoparticles (sshLNPs) constitute next-generation non-viral vectors able to retain the integrity and stability of constructs and to accommodate considerable payloads of biologicals, without requiring cold-chain storage. sshLNP was complexed with a small interfering RNA (siRNA) specifically designed against the human CLCN7G215R mRNA. When tested via single intraperitoneal injection in pre-puberal autosomal dominant osteopetrosis type 2 (ADO2) mice, carrying a heterozygous mutation of the Clcn7 gene (Clcn7G213R), sshLNP, this significantly downregulated the Clcn7G213R related mRNA levels in femurs at 48 h. Confirmatory results were observed at 2 weeks and 4 weeks after treatments (3 intraperitoneal injections/week), with rescue of the bone phenotype and demonstrating safety. The pre-clinical results will enable advanced preclinical development of RNA-based therapy for orphan and genetic skeletal disorders by safely and effectively delivering biologicals of interest to cure human systemic conditions.